2011 IEEE Electrical Power and Energy Conference, EPEC 2011 - Perera, L.; Ledwich, G.; Ghosh, Arindam (-, 2011)
The potential of distributed reactive power control to improve the voltage profile of radial distribution feeders has been reported in literature by few authors. However, the multiple inverters injecting or absorbing reactive power across a distribution feeder may introduce control interactions and/or voltage instability. Such controller interactions can be alleviated if the inverters are allowed to operate on voltage droop. First, the paper demonstrates that a linear shallow droop line can maintain the steady state voltage profile close to reference, up to a certain level of loading. Then, impacts of the shallow droop line control on line losses and line power factors are examined. Finally, a piecewise linear droop line which can achieve reduced line losses and close to unity power factor at the feeder source is proposed.